Rancang Bangun Sistem M-COMOS (Mobile Control Motorcycle System ) Berbasis Arduino - Khoirul Anam; Zuly Budiarso (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
A motorcycle security system is a very important system for vehicle owners, while the security system provided by motorcycle companies is considered not able to overcome it. In this study, an M-Comos system (Mobile Control for Motorcycle System) is created, which is a motor vehicle security device that can be controlled remotely and can track where the vehicle is when it is lost or stolen via GPS. By using the Arduino uno microcontroller as the central controller and the SIM800L module to transmit data over the GPRS communication network, then using the command input from the Blynk Application as the device controller.